2003
DOI: 10.1097/01.tp.0000061490.85273.29
|View full text |Cite
|
Sign up to set email alerts
|

An extraperitoneal isolated vascularized bone marrow transplant model in the rat

Abstract: An isolated vascularized bone marrow transplant (iVBMT) model was previously developed in the rat to specifically study the role of bone marrow and its environment in a composite tissue allotransplant. An extraperitoneal model was successfully created to avoid laparotomy and cross-clamping of the great vessels. The extraperitoneal iVBMT model consisted of a left donor femur that was harvested with its nutrient vessels, anastomosed to the right femoral vessels in a syngeneic host, and then placed subcutaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…Although only a few studies have presented the results of isolated femur allotransplantations, 12,19,21,22 researchers are familiar with this source because of limb allograft studies in which the femur is considered to be the VBM source. The femur receives its blood supply from four arteries: the medial and lateral circumflex arteries, the superior genicular artery, and the muscular branch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although only a few studies have presented the results of isolated femur allotransplantations, 12,19,21,22 researchers are familiar with this source because of limb allograft studies in which the femur is considered to be the VBM source. The femur receives its blood supply from four arteries: the medial and lateral circumflex arteries, the superior genicular artery, and the muscular branch.…”
Section: Discussionmentioning
confidence: 99%
“…In the donor rat, the femur (the source of bone marrow) was harvested from the right side as described by Tai et al 19 The whole hind limb and the inguinal regions were shaved and cleaned with an antiseptic iodine solution. The rat was anesthetized with an intraperitoneal injection of pentobarbital (40 mg/kg) and was placed in the supine position.…”
Section: Operative Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…2, top). Vascularized femur dissection and transplantation proceeded as previously described by Suzuki et al, 16 later refined by Siemionow et al, 12 and further developed by Tai et al, 17 who placed the transplanted bone into a subcutaneous groin pocket. Briefly, the investing femoral musculature was dissected taking care to preserve both the periosteum and the nourishing vasculature (lateral femoral circumflex and superficial circumflex iliac vessels).…”
Section: Vascularized Siea/femur Transplantationmentioning
confidence: 99%
“…Suzuki et al 113 described a vascularized femoral BM transplant model and concluded that it was more useful than limb and sternum transfers in VBMT; and because this model did not include any tissue as additional bone, it was comparatively simple. Tai et al 114 introduced some modifications in this surgical procedure. Instead of using the abdominal cavity of the recipient, Tai et al placed the femoral bone into a subcutaneous pocket created in the anterior abdominal wall of the recipient in order to circumvent the need for laporotomy.…”
Section: Other Composite Tissue Transplantation Modelsmentioning
confidence: 99%